A cementing construction process for high deviation well

By combining oscillating cleaning with electrochemical, catalytic decomposition, and ion exchange processes, the problem of difficult annular cleaning in highly deviated wells has been solved, achieving efficient removal of mud cake and chemical deposits, and improving the cement slurry bonding strength and wellbore sealing.

CN120867675BActive Publication Date: 2025-11-28SHENGLI OILFIELD BOHAI CEMENTING ENG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511373879.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2025-11-28
Estimated Expiration
2045-09-25

AI Technical Summary

Technical Problem

Highly deviated wells present challenges in annular cleaning during cementing operations. Existing cleaning processes are insufficient to completely remove mud cake and chemical deposits, resulting in poor bonding quality between the cement slurry, casing, and formation.

Method used

The cleaning solution is purified by oscillating cleaning combined with electrochemical, catalytic decomposition and ion exchange processes. The oscillation effect of periodically changing the circulation pressure and flow rate is achieved by adding sodium chloride electrolyte solution and iron oxide catalyst, using an electrode device to establish a DC electric field, and using zeolite molecular sieves for ion exchange, and circulating and purifying the cleaning solution in real time.

Benefits of technology

It significantly improves the removal rate of annular pollutants, has a remarkable effect on decomposing organic polymers, reduces the electrostatic adsorption force between pollutants and the well wall, improves cleaning efficiency and bonding strength, and ensures the integrity of the well casing seal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120867675B_ABST
    Figure CN120867675B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of oil engineering cementing, and discloses a cementing construction process for high-deviation wells, which comprises the following steps: oscillation type basic cleaning, stripping of well wall pollutants by generating oscillation effect through periodical change of circulating pressure and flow rate; electrochemical synergistic cleaning, decomposition of organic pollutants by electrolysis; catalytic decomposition cleaning, acceleration of mud cake polymer molecular chain rupture; ion exchange treatment, change of charge distribution state of pollutants; and circulating purification step, real-time removal of reaction products and restoration of reaction conditions. The present application realizes physical-chemical composite cleaning through synergistic effect of multiple processes, completely removes annular pollutants of high-deviation wells, and significantly improves cementing quality and wellbore sealing performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of oil engineering cementing, more particularly, it relates to a cementing construction process for high-deviation wells. BACKGROUND

[0002] High-deviation wells face the technical challenge of annular cleaning difficulty in cementing construction due to the complex wellbore trajectory and large inclination angle. In the prior art, the traditional annular cleaning process mainly relies on mechanical scouring to remove wall attachments, but in the application of high-deviation wells, the problem of incomplete removal of mud cake and serious sediment residue often occurs, resulting in poor cementing interface quality between the cement slurry, casing and formation.

[0003] The existing oscillation cleaning process can improve the cleaning effect to a certain extent by periodically changing the circulating pressure and flow rate to generate oscillation, but this method is a single physical cleaning, and the cleaning effect is limited when facing complex mud cakes containing organic polymers and chemical sediments with strong adhesion in high-deviation wells, and it is difficult to completely remove them.

[0004] The existing cleaning process cannot completely remove the complex pollutants in the annulus of high-deviation wells, the single physical cleaning has poor decomposition effect on organic polymers, and the multi-process coordination causes secondary pollution of reaction products. SUMMARY

[0005] In order to solve the above technical problems, the present application provides a cementing construction process for high-deviation wells, comprising the following steps:

[0006] Step S1: injecting a cleaning fluid into the annulus of the high-deviation well, and periodically changing the circulating pressure and flow rate to generate oscillation, so that the wall attached pollutants fall into the cleaning fluid;

[0007] Step S2: while oscillation cleaning, an electrochemical cleaning process is implemented in the annulus, sodium chloride electrolyte solution is added to the cleaning fluid, a direct current field is established by the electrode device, and the electrolytic action is used to decompose the organic pollutants in the annulus;

[0008] Step S3: simultaneously implementing a catalytic decomposition process, adding an iron oxide catalyst to the cleaning fluid, and using the synergistic effect of the oxidizing substance generated by the electrochemical process to accelerate the molecular chain breaking process of the polymer in the mud cake;

[0009] Step S4: cooperating with the implementation of an ion exchange process, adding zeolite molecular sieve to the cleaning fluid, and ion exchange reaction occurs between the zeolite molecular sieve and the cationic groups on the surface of the pollutants to reduce the electrostatic adsorption force between the pollutants and the well wall;

[0010] Step S5: Implementing a circulating purification process to remove the intermediate products generated by the electrochemical reaction and catalytic decomposition in real time through a circulating device, and periodically adjusting the pH value, ion concentration and oxidation-reduction potential of the cleaning fluid.

[0011] Preferably: In step S1, the fluid pressure in the annulus periodically fluctuates within the range of 0.5-2.0 MPa, and the flow rate periodically changes within the range of 0.3-1.5 m / s, with an oscillation duration of 20-45 minutes.

[0012] Preferably: In step S2, the mass concentration of the sodium chloride electrolyte solution is 3-8 g / L, the direct current field voltage is 5-15 V, the current density is controlled at 10-30 mA / cm², and the electrolysis treatment time is 15-35 minutes.

[0013] Preferably: In step S3, the iron oxide catalyst is nano α-Fe2O3 with a particle size of 20-80 nm and a specific surface area of 80-200 m² / g, and the mass concentration is 0.1-0.5 g / L.

[0014] Preferably: In step S4, the zeolite molecular sieve is a 4A type sodium-based zeolite molecular sieve with a pore size of 4Å and a specific surface area of 500-800 m² / g, and the mass concentration is 2-6 g / L.

[0015] Preferably: In step S5, the circulating purification process includes product separation and circulation operation and environmental regeneration operation. The product separation and circulation operation removes solid particles and chemical precipitates through a precision filter and a cyclone separation device. The environmental regeneration operation adjusts the pH value to 6.5-8.5, controls the total dissolved solids concentration within the range of 100-500 mg / L, and maintains the oxidation-reduction potential at 200-400 mV.

[0016] Preferably: The cleaning fluid is a water-based cleaning solution with a density of 1.05-1.15 g / cm³ and a viscosity of 10-30 mPa·s, and the temperature is controlled at 60-90°C.

[0017] Preferably: The oscillation effect is achieved by controlling the start-stop state and speed variation of the screw pump. The fluid pressure periodically fluctuates at a frequency of 3-8 times per minute, and the flow rate periodically changes at a frequency of 5-12 times per minute.

[0018] Preferably: The electrode device is a 316L stainless steel electrode with an electrode spacing of 5-15 cm, and the electrochemical reaction is carried out at a pH value of 7.0-8.5.

[0019] Preferably: The precision filter has a pore size of 10-50 μm, the cyclone separation device has a settling velocity of 0.5-2.0 mm / s, the separation efficiency reaches 90-98%, and the environmental adjustment is performed every 30-60 minutes.

[0020] The beneficial effects of this invention are as follows:

[0021] The cleaning effect is significantly improved: the four cleaning mechanisms of physical oscillation, electrochemical decomposition, catalytic reaction and ion exchange work synergistically to achieve an atmospheric pollutant removal rate of 90-98%, which is 25-33% higher than the 65-75% removal rate of traditional single oscillation cleaning process. The residual pollutant particles are measured to be less than 10μm in diameter and less than 100 particles / cm³ by laser particle size analyzer.

[0022] Strong ability to treat complex pollutants: Electrochemical and catalytic decomposition processes achieve a decomposition rate of 80-95% for organic polymers, with the degree of molecular weight reduction determined by gel permeation chromatography; Ion exchange processes reduce the surface charge density of charged pollutants by 60-80%, as determined by a Zeta potential analyzer; Expanding the applicability of cleaning processes to different pollutants, effectively treating various pollutants with densities of 1.2-2.5 g / cm³ and adhesion strengths of 50-500 kPa.

[0023] Continuous and stable cleaning performance: The circulating purification process ensures that the cleaning effect remains stable during 120 minutes of continuous operation, with a cleaning efficiency decrease of less than 5%; the environmental regeneration operation controls pH fluctuations within ±0.2 and ion concentration changes of less than 10%, with various indicators measured in real time through an online monitoring system.

[0024] Significant synergistic enhancement: The synergistic effect of various process elements increases the mass transfer coefficient by 2-4 times and the reaction rate constant by 3-6 times, as determined by mass transfer experiments and reaction kinetic analysis; the overall cleaning efficiency reaches 3.5-4.2 times that of a single process, achieving a synergistic multiplier effect.

[0025] Cementing quality assurance: After annular cleaning, the surface roughness Ra value of the well wall is reduced to 2-8μm, the cement slurry bonding strength is increased by 15-30% to 2.5-4.5MPa, and the wellbore sealing integrity reaches over 99%. Attached Figure Description

[0026] Figure 1 It is a comparison of mass transfer coefficients for different processes;

[0027] Figure 2 It is a comparison of reaction rate constants for different processes;

[0028] Figure 3 This is a comparison of cleaning efficiency over time;

[0029] Figure 4 It is a comparison of pH value changes over time;

[0030] Figure 5 It is a comparison of the total dissolved solids concentration over time. Detailed Implementation

[0031] The subject matter described herein will now be discussed with reference to example implementations. It should be understood that the discussion of these implementations is merely meant to provide a better understanding of the subject matter described herein and can be changed in ways not for departing from the scope of the protection of the present specification. Various processes or components can be omitted, substituted, or added according to desired implementations. Additionally, features described in some examples can be combined in other examples.

[0032] Example 1

[0033] A cementing operation process for high-deviation wells is proposed in the present example, comprising the following steps:

[0034] Step S1: injecting a cleaning fluid into the annulus of the high-deviation well, and generating an oscillation effect by periodically changing the circulating pressure and flow rate, so that the contaminants attached to the well wall fall off into the cleaning fluid;

[0035] The fluid pressure in the annulus periodically fluctuates in the range of 0.5-1.0 MPa, and the flow rate periodically changes in the range of 0.3-0.9 m / s, and the oscillation duration is 32 minutes;

[0036] The cleaning fluid is a water-based cleaning fluid, with a density of 1.05-1.10 g / cm³, a viscosity of 10-20 mPa·s, and a temperature controlled at 60-70 °C;

[0037] The oscillation effect is achieved by controlling the start-stop state and rotational speed of the screw pump, and the fluid pressure periodically fluctuates at a frequency of 5 times per minute, and the flow rate periodically changes at a frequency of 8 times per minute.

[0038] Step S2: while oscillation cleaning, an electrochemical cleaning process is implemented in the annulus, a sodium chloride electrolyte solution is added to the cleaning fluid, a direct current electric field is established by an electrode device, and organic contaminants in the annulus are decomposed by electrolysis;

[0039] The mass concentration of the sodium chloride electrolyte solution is 3-5 g / L, the voltage of the direct current electric field is 5-10 V, the current density is controlled at 10-20 mA / cm², and the electrolysis treatment time is 15-25 minutes;

[0040] The electrode device is a 316L stainless steel electrode, the electrode spacing is 5-10 cm, and the electrochemical reaction is carried out at a pH value of 7.0-7.5.

[0041] Step S3: simultaneously implementing a catalytic decomposition process, adding an iron oxide catalyst to the cleaning fluid, and using its synergistic effect with the oxidizing substances generated by the electrochemical process to accelerate the molecular chain breaking process of the polymers in the mud cake;

[0042] The iron oxide catalyst is nano alpha-Fe2O3, with a particle size of 20-50 nm, a specific surface area of 80-140 m2 / g, and a mass concentration of 0.1-0.3 g / L.

[0043] Step S4: Perform ion exchange process, add zeolite molecular sieve to the cleaning fluid, and perform ion exchange reaction with the cationic groups on the surface of the contaminants to reduce the electrostatic adsorption force between the contaminants and the well wall.

[0044] The zeolite molecular sieve is a 4A type sodium-based zeolite molecular sieve with a pore size of 4 Å and a specific surface area of 500-700 m2 / g, and a mass concentration of 2-4 g / L.

[0045] Step S5: Perform cyclic purification process, real-time removal of intermediate products generated by electrochemical reaction and catalytic decomposition through circulation device, periodic adjustment of pH value, ion concentration and redox potential of cleaning fluid;

[0046] The cyclic purification process includes product separation and circulation operation and environment regeneration operation. The product separation and circulation operation removes solid particles and chemical precipitates through a precision filter and a cyclone separation device. The environment regeneration operation adjusts the pH value to 6.5-7.5, controls the total dissolved solids concentration in the range of 100-300 mg / L, and maintains the oxidation-reduction potential at 200-300 mV.

[0047] The pore size of the precision filter is 10-30 μm, the settling velocity of the cyclone separation device is 0.5-1.5 mm / s, the separation efficiency reaches 90-94%, and the environment is adjusted every 30-40 minutes.

[0048] Example 2

[0049] The difference between this embodiment and Example 1 is:

[0050] Step S1: The annulus fluid pressure is periodically fluctuated in the range of 1.0-2.0 MPa, and the flow rate is periodically changed in the range of 0.9-1.5 m / s, with a duration of 20 minutes.

[0051] The cleaning fluid is a water-based cleaning fluid with a density of 1.10-1.15 g / cm3, a viscosity of 20-30 mPa·s, and a temperature controlled at 70-90℃.

[0052] The fluid pressure is periodically fluctuated at a frequency of 3-8 times per minute, and the flow rate is periodically changed at a frequency of 5 times per minute.

[0053] Step S2: The mass concentration of the sodium chloride electrolyte solution is 5-8 g / L, the direct current field voltage is 10-15 V, the current density is controlled at 20-30 mA / cm2, and the electrolysis treatment time is 25-35 minutes.

[0054] The electrode spacing is 10-15 cm, and the electrochemical reaction is carried out at a pH value of 7.5-8.5.

[0055] Step S3: The iron oxide catalyst is nano α-Fe2O3, with a particle size of 50-80 nm, a specific surface area of 140-200 m² / g, and a mass concentration of 0.3-0.5 g / L.

[0056] Step S4: The zeolite molecular sieve is a 4A type sodium-based zeolite molecular sieve, with a pore size of 4 Å, a specific surface area of 700-800 m² / g, and a mass concentration of 4-6 g / L.

[0057] Step S5: The environmental regeneration operation adjusts the pH value to 7.5-8.5, controls the total dissolved solid concentration in the range of 300-500 mg / L, and maintains the oxidation-reduction potential at 300-400 mV.

[0058] The pore size of the precision filter is 30-50 μm, the settling velocity of the cyclone separation device is 1.5-2.0 mm / s, the separation efficiency reaches 94-98%, and the environmental adjustment is performed every 40-60 minutes.

[0059] Example 3

[0060] The difference between this example and Example 1 is:

[0061] Step S1: The fluid pressure in the annulus periodically fluctuates in the range of 0.5-2.0 MPa, and the flow rate periodically changes in the range of 0.3-1.5 m / s, with an oscillation duration of 45 minutes.

[0062] The cleaning fluid is a water-based cleaning solution with a density of 1.05-1.15 g / cm³ and a viscosity of 10-30 mPa·s, and the temperature is controlled at 60-90 °C.

[0063] The fluid pressure periodically fluctuates at a frequency of 3-8 times per minute, and the flow rate periodically changes at a frequency of 12 times per minute.

[0064] Step S2: The mass concentration of the sodium chloride electrolyte solution is 3-8 g / L, the direct current electric field voltage is 5-15 V, the current density is controlled at 10-30 mA / cm², and the electrolysis treatment time is 15-35 minutes.

[0065] The electrode spacing is 5-15 cm, and the electrochemical reaction is carried out at a pH value of 7.0-8.5.

[0066] Step S3: The iron oxide catalyst is nano α-Fe2O3, with a particle size of 20-80 nm, a specific surface area of 80-200 m² / g, and a mass concentration of 0.1-0.5 g / L.

[0067] Step S4: The zeolite molecular sieve is a 4A type sodium-based zeolite molecular sieve with a pore size of 4 Å, a specific surface area of 500-800 m² / g, and a mass concentration of 2-6 g / L.

[0068] Step S5: The environmental regeneration operation adjusts the pH value to 6.5-8.5, controls the total dissolved solid concentration in the range of 100-500 mg / L, and maintains the oxidation-reduction potential at 200-400 mV.

[0069] The precision filter has a pore size of 10-50 μm, the settling velocity of the cyclone separation device is 0.5-2.0 mm / s, the separation efficiency reaches 90-98%, and the environmental adjustment is performed every 30-60 minutes.

[0070] Example 4

[0071] In this example, a cementing construction process for a high-deviation well is proposed, and the key material selection criteria and alternative solutions in this example are as follows:

[0072] The cleaning fluid selection criteria are as follows: the water-based cleaning fluid density is selected to be 1.05-1.15 g / cm³ based on the annular flow characteristics of the high-deviation well. If the density is too low (<1.05 g / cm³), the carrying capacity is insufficient, and if the density is too high (>1.15 g / cm³), the circulating pressure consumption increases. The viscosity is selected to be 10-30 mPa·s to balance the flowability and suspension capacity. Alternative solutions include bio-based cleaning fluid or synthetic cleaning fluid, which have similar effects but different costs.

[0073] The electrolyte selection criteria are as follows: the sodium chloride concentration is 3-8 g / L based on the balance between conductivity and electrolytic efficiency. If the concentration is too low, the conductivity is insufficient, and if it is too high, excessive chlorine gas will be generated. Alternative solutions include potassium chloride (3-10 g / L) or sodium sulfate (2-6 g / L), but sodium chloride has the lowest cost and stable effect.

[0074] The catalyst selection criteria are as follows: nano α-Fe2O3 is selected based on its stability and catalytic activity in an oxidation environment, and the particle size is 20-80 nm to ensure dispersibility and active surface area. Alternative solutions include nano TiO2 (which requires an additional light source) or MnO2 (which has a higher cost), but Fe2O3 has the best overall cost performance.

[0075] The ion exchange material selection criteria are as follows: 4A type zeolite is selected based on its 4 Å pore size matching the target ion size and excellent oxidation resistance. Alternative solutions include 5A type zeolite or 13X zeolite, but 4A type has the best selectivity.

[0076] The cementing construction process in this example includes the following specific steps:

[0077] Step S1: Oscillating basic cleaning

[0078] Before cement slurry injection, a cleaning fluid is injected into the annulus of the highly deviated well, the cleaning fluid is a water-based cleaning fluid with a density of 1.05-1.15 g / cm3 and a viscosity of 10-30 mPa·s, and an oscillation effect is generated by periodically changing the circulating pressure and flow rate. Specifically, under the condition of a temperature of 60-90℃, by controlling the start-stop state and rotating speed variation of a screw pump with a discharge of 150-300 L / min, the fluid pressure in the annulus is periodically fluctuated in the range of 0.5-2.0 MPa with a frequency of 3-8 times per minute, and the flow rate is periodically changed in the range of 0.3-1.5 m / s with a frequency of 5-12 times per minute, the oscillation duration is 20-45 minutes, and a composite oscillation effect of pressure pulse and flow rate oscillation is formed.

[0079] The oscillation effect generates periodic mechanical impact force and shear force on the well wall mud cake and deposits, the mechanical impact force reaches 50-150 N / cm2, and the adhered contaminants fall off from the well wall surface into the cleaning fluid. The cleaning fluid containing suspended contaminant particles with a concentration of 5-25 g / L and the well wall surface after removing the surface contaminants with a roughness reduction of 30-60% are obtained.

[0080] Step S2: electrochemical synergistic cleaning

[0081] While the oscillation cleaning is performed, an electrochemical cleaning process is implemented in the annulus.

[0082] Specifically, an analytical pure sodium chloride electrolyte solution with a mass concentration of 3-8 g / L is added to the cleaning fluid, a 5-15 V direct current electric field is established in the annulus by a 316L stainless steel electrode device with a spacing of 5-15 cm, the current density is controlled at 10-30 mA / cm2, the electrolysis treatment time is 15-35 minutes, and the organic contaminants in the annulus are decomposed by electrolysis.

[0083] The electrochemical reaction is performed under the condition of a pH value of 7.0-8.5, the organic polymer molecular chain is broken into small molecular compounds with a molecular weight of less than 1000 Da, the electrolysis efficiency reaches 65-85%, and the concentration of the oxidizing substances such as hypochlorite generated at the same time is 50-200 mg / L to further oxidize and decompose the contaminants.

[0084] The oscillation effect enhances the mixing and mass transfer process of the electrolyte and the contaminants, the mass transfer coefficient is increased by 2-4 times, and the electrochemical decomposition efficiency is improved. The electrolysis treatment fluid containing small molecular organic compounds with a concentration of 200-800 mg / L and oxidation products and the organic contaminant residues with a molecular weight reduction of 60-80% are obtained.

[0085] Step S3: catalytic decomposition cleaning

[0086] The catalytic decomposition process is implemented synchronously, and the nano iron oxide catalyst with a mass concentration of 0.1-0.5 g / L is put into the cleaning fluid, the catalyst is α-Fe2O3 with a particle size of 20-80 nm and a specific surface area of 80-200 m² / g, and the catalytic decomposition process is implemented in cooperation with the oxidizing substances generated in the electrochemical process to accelerate the molecular chain breaking process of the polymer in the mud cake. Under the condition of a temperature of 65-85 ℃, the nano iron oxide catalyst is fully contacted with the surface of the mud cake under the diffusion enhancement effect of the oscillation, the catalytic decomposition process catalyzes the oxidation and breaking reaction of the polymer molecular chain by the oxidizing substances such as hypochlorous acid, the reaction time is 10-25 minutes, the catalytic efficiency reaches 70-90%, and the macromolecular polymer with a molecular weight greater than 10,000 Da is decomposed into small molecular compounds with a molecular weight less than 2,000 Da.

[0087] The catalytic decomposition process reduces the bonding strength of the mud cake to 30-50% of the original strength, the bonding strength is reduced from the original 150-300 kPa to 45-150 kPa through the universal testing machine, the mechanical force required for the oscillation cleaning is reduced, and the stripping efficiency of the physical cleaning is improved. The catalytic reaction liquid containing the low-molecular-weight organic compounds with a concentration of 300-1,200 mg / L and the mud cake with a loose structure, reduced bonding strength and improved porosity of 35-55% are obtained.

[0088] Step S4: ion exchange treatment

[0089] The ion exchange process is implemented in cooperation, and the 4A type sodium-based zeolite molecular sieve with a mass concentration of 2-6 g / L is added to the cleaning fluid, the zeolite molecular sieve has a pore size of 4 Å, a specific surface area of 500-800 m² / g and a cation exchange capacity of 280-350 meq / 100 g, and the charge distribution state of the pollutants is changed.

[0090] Specifically, under the condition of a temperature of 60-85 ℃ and a pH value of 6.0-8.0, the 4A type zeolite molecular sieve has good oxidation resistance and can exist stably in the oxidizing environment, and the ion exchange reaction occurs between the zeolite molecular sieve and the cation groups on the surface of the pollutants, the ion exchange time is 8-20 minutes, the exchange efficiency reaches 75-95%, the Ca 2+ , Mg 2+ and other multivalent cations on the surface of the pollutants are replaced by Na + and other monovalent cations, the surface charge density of the pollutants is reduced from the original 15-40 μC / cm² to 3-12 μC / cm², the electrostatic adsorption force between the pollutants and the well wall is reduced, the wetting contact angle between the pollutants and the cleaning fluid is reduced from 120-150° to 60-90° in the ion exchange process, and the detachment ability of the pollutants under the oscillation is enhanced.

[0091] The above four steps work together to form a multiple cleaning effect of mechanical peeling, electrochemical decomposition, catalytic weakening, and ion activation. The contaminated particles and Na + The ion concentration is 800-2000 mg / L, Ca 2+ and Mg 2+ The ion concentration is reduced to 50 mg / L or less.

[0092] Step S5: Circulating purification

[0093] The circulating purification process is implemented, including product separation circulation operation and environmental regeneration operation.

[0094] The product separation circulation operation removes the intermediate products generated by the electrochemical reaction and catalytic decomposition in real time through a centrifugal pump circulating device with a circulating flow of 100-200 L / min, preventing the accumulation of secondary pollution in the wellbore. Specifically, the cleaning fluid containing reaction products is pumped out from the annulus, passes through a precision filter with a pore size of 10-50 μm and a cyclone separation device with a settling velocity of 0.5-2.0 mm / s to remove solid particles and chemical precipitates, with a separation efficiency of 90-98% and a treatment time of 5-15 minutes per cycle. The treated fluid is re-injected into the annulus for continuous cleaning.

[0095] The environmental regeneration operation periodically adjusts the pH value of the cleaning fluid to 6.5-8.5 (monitored by a pH electrode in real time, with an accuracy of ±0.1), the total dissolved solid concentration to 100-500 mg / L (monitored by a conductivity meter), and the oxidation-reduction potential to 200-400 mV (monitored by an ORP electrode), every 30-60 minutes, to restore the appropriate conditions for electrochemical reaction, catalytic reaction, and ion exchange reaction, ensuring the continuous progress of the cleaning process. The circulating cleaning fluid with a solid impurity content of less than 0.1% and solid waste with a moisture content of 5-15% are obtained, and the cleaning fluid environment with pH value, total dissolved solid concentration, and oxidation-reduction potential adjusted to the required range and stability maintained at 95% or above is obtained.

[0096] Experimental verification

[0097] Experiment 1: Comparison of cleaning effect of multi-process synergy

[0098] Experimental purpose:

[0099] To verify the improvement of cleaning effect of multi-process synergy compared to single cleaning process and prove the technical advantages of synergy.

[0100] Experimental materials and equipment:

[0101] Simulated high-angle wellbore device (well inclination angle 60°, length 2 m, inner diameter 150 mm);

[0102] Artificially prepared mud cake sample (density 1.8 g / cm³, thickness 3-5 mm, containing organic polymer PAM 0.3%);

[0103] Cleaning fluid (density 1.10 g / cm³, viscosity 20 mPa·s);

[0104] Screw pump (displacement 200 L / min);

[0105] Electrochemical device (316L stainless steel electrode, spacing 10 cm);

[0106] Nano α-Fe2O3 catalyst (particle size 50 nm);

[0107] 4A type zeolite molecular sieve (specific surface area 650 m² / g);

[0108] Laser particle size analyzer, scanning electron microscope, surface profiler.

[0109] Experimental steps:

[0110] Uniformly coat the mud cake sample on the inner wall of the simulated wellbore, with a thickness controlled at 4±0.5 mm;

[0111] Set up 5 comparison groups:

[0112] Group 1: only oscillation cleaning (pressure 1.2 MPa, flow rate 0.8 m / s, frequency 6 times / min);

[0113] Group 2: oscillation + electrochemistry (sodium chloride 5 g / L, voltage 10 V, current density 20 mA / cm²);

[0114] Group 3: oscillation + catalysis (ferric oxide 0.3 g / L, temperature 75°C);

[0115] Group 4: oscillation + ion exchange (zeolite 4 g / L);

[0116] Group 5: four-process synergy (oscillation + electrochemistry + catalysis + ion exchange);

[0117] Each group has a cleaning time of 30 minutes, with a temperature control of 75±2°C;

[0118] Post-cleaning detection: contaminant removal rate, wellbore surface roughness, residual particle number.

[0119] Experimental results:

[0120]

[0121] Result analysis:

[0122] The experimental results show that the pollutant removal rate of the four-process synergistic cleaning is 22.3% higher than that of single oscillation cleaning and 10.9% higher than that of the best double-process combination, verifying the significant advantage of multi-process synergy.

[0123] Experiment two: synergistic enhancement verification experiment.

[0124] Experimental purpose:

[0125] Quantitative determination of the change of mass transfer coefficient and reaction rate constant in multi-process synergistic process to verify the synergistic enhancement mechanism.

[0126] Experimental materials and equipment

[0127] Reaction kettle device (volume 5L, controllable temperature, stirring, sampling);

[0128] Organic polymer standard sample (polyacrylamide, molecular weight 12000Da);

[0129] Pollutant simulation solution (COD 800mg / L, suspended solids 500mg / L);

[0130] Dissolved oxygen tester, COD tester, molecular weight tester (GPC);

[0131] Mass transfer coefficient determination device, reaction kinetics analysis system.

[0132] Experimental steps:

[0133] Prepare standard pollutant solution, COD controlled at 800±20mg / L;

[0134] Determine the mass transfer coefficient and reaction rate of single process and synergistic process respectively:

[0135] Test group A: single electrochemical treatment;

[0136] Test group B: single catalytic oxidation treatment;

[0137] Test group C: electrochemistry + catalysis synergistic treatment;

[0138] Test group D: oscillation + electrochemistry + catalysis synergistic treatment;

[0139] Calculate the mass transfer coefficient kLa by the dissolved oxygen consumption rate;

[0140] Calculate the reaction rate constant k by the change of pollutant concentration;

[0141] Each group is repeated 3 times, and the average value is taken;

[0142] Experimental results:

[0143] Figure 1The different process mass transfer coefficients are compared.

[0144] Figure 2 The different process reaction rate constants are compared.

[0145] Synergistic enhancement factor analysis:

[0146]

[0147] Result analysis:

[0148] The experimental results confirm the synergistic enhancement effect: four-process synergy increases the mass transfer coefficient by 3.8 times and the reaction rate constant by 3.5 times.

[0149] Experiment three: continuous purification stability test.

[0150] Experimental purpose:

[0151] To verify the stability of the cleaning effect and the control effect of environmental parameters of the continuous purification process in long-term continuous operation.

[0152] Experimental materials and equipment:

[0153] Continuous circulation cleaning test device (circulation flow rate 150 L / min);

[0154] Precision filter (pore size 30 μm) and cyclone separator;

[0155] Online monitoring system (pH meter, conductivity meter, ORP meter);

[0156] Automatic dosing system (pH adjuster, electrolyte supplement);

[0157] Continuous pollutant dosing device;

[0158] Real-time data acquisition system.

[0159] Experimental steps:

[0160] Start the continuous circulation cleaning system, and set the initial conditions:

[0161] Cleaning liquid temperature: 75℃;

[0162] pH value: 7.2;

[0163] Total dissolved solids concentration: 250 mg / L;

[0164] Oxidation-reduction potential: 320 mV;

[0165] Run continuously for 120 minutes, and add standard pollutants (COD 100 mg / L) every 10 minutes;

[0166] Real-time monitoring of cleaning efficiency, pH value change, ion concentration change;

[0167] Test the performance change under the conditions of circulating purification and non-circulating purification respectively.

[0168] Experimental results:

[0169] The long-term stability test results are shown in Figure 3 Comparison of cleaning efficiency change over time, Figure 4 Comparison of pH value change over time, and Figure 5 Comparison of total dissolved solids concentration change over time.

[0170] Comparison and analysis of stability indicators:

[0171]

[0172] Result analysis:

[0173] The experimental results verify the significant effect of the circulating purification process: in 120 minutes of continuous operation, the cleaning efficiency with circulating purification is stable at 93.7-94.5%, with a decay of less than 1%; while the cleaning efficiency without circulating purification decays from 94.5% to 63.7%, with a decay of 30.8%. The circulating purification process successfully maintains the stability of key parameters such as pH value and ion concentration.

[0174] The above describes embodiments of the present application, but the embodiments are not limited to the specific implementation described above, which is only illustrative and not restrictive. Those skilled in the art can make more forms of equivalent embodiments under the inspiration of the embodiments, which are all within the protection of the embodiments.

Claims

1. A cementing construction process for highly deviated wells, characterized in that, Includes the following steps: Step S1: Inject cleaning fluid into the annulus of a highly deviated well. Use periodic changes in circulation pressure and flow rate to generate an oscillation effect, causing contaminants attached to the well wall to fall off and enter the cleaning fluid. Step S2: While performing oscillating cleaning, an electrochemical cleaning process is carried out in the annulus. Sodium chloride electrolyte solution is added to the cleaning fluid, and a DC electric field is established through an electrode device to decompose organic pollutants in the annulus by electrolysis. The mass concentration of sodium chloride electrolyte solution is 3-8 g / L, the DC electric field voltage is 5-15 V, the current density is controlled at 10-30 mA / cm², and the electrolysis treatment time is 15-35 minutes. Step S3: Simultaneously implement the catalytic decomposition process by adding an iron oxide catalyst to the cleaning fluid. Utilize its synergistic effect with the oxidizing substances generated during the electrochemical process to accelerate the molecular chain breakage of polymers in the sludge cake. The iron oxide catalyst is nano-α-Fe2O3 with a particle size of 20-80 nm, a specific surface area of ​​80-200 m² / g, and a mass concentration of 0.1-0.5 g / L. Step S4: In conjunction with the implementation of the ion exchange process, zeolite molecular sieves are added to the cleaning fluid to undergo ion exchange reactions with the cationic groups on the surface of the contaminants, thereby reducing the electrostatic adsorption force between the contaminants and the well wall; the zeolite molecular sieve is a type 4A sodium-based zeolite molecular sieve with a pore size of 4 Å, a specific surface area of ​​500-800 m² / g, and a mass concentration of 2-6 g / L. Step S5: Implement a circulating purification process, using a circulating device to remove intermediate products generated by electrochemical reactions and catalytic decomposition in real time, and periodically adjust the pH, ion concentration, and redox potential of the cleaning solution.

2. The cementing construction process according to claim 1, characterized in that, In step S1, the fluid pressure in the annulus fluctuates periodically within the range of 0.5-2.0 MPa, the flow velocity changes periodically within the range of 0.3-1.5 m / s, and the oscillation duration is 20-45 minutes.

3. The cementing construction process according to claim 1, characterized in that, In step S5, the circulating purification process includes product separation and circulation operation and environmental regeneration operation. The product separation and circulation operation removes solid particles and chemical precipitates through a precision filter and a cyclone separator. The environmental regeneration operation adjusts the pH value to 6.5-8.5, controls the total dissolved solids concentration in the range of 100-500 mg / L, and maintains the oxidation-reduction potential in the range of 200-400 mV.

4. The cementing construction process according to claim 1, characterized in that, The cleaning fluid is a water-based cleaning solution with a density of 1.05-1.15 g / cm³, a viscosity of 10-30 mPa·s, and a temperature controlled at 60-90℃.

5. The cementing construction process according to claim 2, characterized in that, The oscillation effect is achieved by controlling the start-stop state and speed change of the screw pump. The fluid pressure fluctuates periodically at a frequency of 3-8 times / minute, and the flow velocity changes periodically at a frequency of 5-12 times / minute.

6. The cementing construction process according to claim 1, characterized in that, The electrode device is a 316L stainless steel electrode with an electrode spacing of 5-15cm, and the electrochemical reaction is carried out under pH conditions of 7.0-8.

5.

7. The cementing construction process according to claim 3, characterized in that, The precision filter has a pore size of 10-50μm, the settling velocity of the cyclone separator is 0.5-2.0mm / s, the separation efficiency reaches 90-98%, and the environment is adjusted every 30-60 minutes.

Citation Information

Patent Citations

  • Universal type scale preventing device

    CN105971560A

  • Method for improving shale gas well oil-string casing well cementation quality

    CN111058796A